İris kolobomlu olgularda sistemik ve oftalmolojik bulgular - (:unkn) unknown (My University, 2013)
Amaç: Okuler kolobom embriyonik optik yarığın kapanma defekti sonucunda oluşan nadir bir malformasyondur. İris, koroid, retina, optik sinir ve siliyer cismi tutabilir. Bu çalışmada kliniğimize başvuran değişik oküler tutulumu olan kolobomlu olguların klinik ozellikleri, eşlik eden bulguları ve takipleri açısından sunulması planlanmıştır. Gereç ve Yöntem: Calışmamızda kliniğimize başvuran ve iris kolobomu tanısı alan 10 olgunun 16 gözü retrospektif olarak değerlendirimiştir. Sonuçlar: Olguların 7 si sporadik, 3ü ailesel idi. Olguların birinde iris kolobomu izole iken, diğerlerinde iris kolobomuna koryoretinal kolobom eşlik etmekte idi. Yedi olguda optik disk tutulumu mevcuttu. Eşlik eden göz bulguları icinde 3 olguda tek taraflı mikroftalmi, 1 olguda tek taraflı anoftalmi, 1 olguda da tek taraflı mikrokornea saptandı. Ailesel olgularda eşlik eden şaşılık mevcuttu. Tart flma: Göz kliniğine başvuran ve kolobom tanısı alan olgularda rutin göz muayenesi tamamlanmalı, refraksiyon kusurları düzeltilmeli, ambliyopi açısından takip edilmeli, varsa eşlik eden şaşılığın cerrahisi uygulanmalı ve takiplerde olası komplikasyonlar

Purpo se: Ocular coloboma is a rare malformation resulting from defective closure of the embryonic optic fissure. It can affect iris, retina, choroid, optic disc or ciliary body. This study reviews the clinical diagnosis and the accompanying ocular and systemic abnormalities in cases of iris coloboma. Material and Method: Sixteen eyes of ten patients referred to our clinic and diagnosed as iris coloboma were included in the study and were reviewed retrospectively. Results: Seven cases were sporadic, and three cases were familial. Isolated iris coloboma was present in only one case, and chorioretinal involvement was present in all the others. Seven cases had involvement of the optic disc. Other ocular anomalies were unilateral microphthalmia in 3 cases, unilateral anophthalmia in 1 case, and unilateral microcornea in one case. Strabismus was present in the familial cases. Discussion: In patients, diagnosed with iris coloboma, routine eye examination should be completed, refractive errors should be corrected, and these patients must be follewed for amblyopia. If strabismus is concominant, surgery can be performed. For potential complications, patients should be checked at regular intervals. (Turk J Ophthalmol 2013; 43: 19-22)
Systemic and ophthalmologic findings in patients with ıris coloboma
Keywords: Göz Hastalıkları